Differentiated legitimacy, differentiated resilience: beyond the natural in 'natural disasters'. Issue 5 (3rd September 2017) - Harrison, Elizabeth; Chiroro, Canford
Abstract : This paper starts with a flood in southern Malawi. Although apparently a 'natural' event, those most affected argued that it was made much worse by the rehabilitation of a nearby irrigation scheme. We use this example to interrogate the current interest in resilience from a perspective informed by political ecology and political economy, arguing that a focus on resilience should not be at the expense of understanding the conditions that shape vulnerability, including the ways in which 'communities' are differentiated. Complex factors are at play – and the ways in which these combine can result in a 'perfect storm' for some individuals and households. These factors include the effects of history combining with ethnicity, of legitimacy influencing voice, and of the interplay of political dynamics at different levels. In particular, processes of commodification have played an important role in shaping how some may benefit at the cost of catastrophic harm to others.